Cloud Computing para el internet de las cosas. Caso de estudio orientado a la agricultura de precisión - Campoverde Marca, Ariel Mauricio (2015)
Precision agriculture is today one of the most advanced technologies to increase the efficiency and productivity of crops through the use of ICT solutions. One of the applied technologies is the wireless sensor network (WSN) to measure variables associated with soil, plant and fruit crops that allow among others, define strategies for irrigation control towards productivity and optimization of vital natural resources such as the water. The case study of this project is applied to control risk of an experimental cocoa plantation. The proposed objective is to define the architecture and components of a Cloud computing to the Internet of Things, acting as Monitoring and Control Center of Telemetry system. This system manages and processes data related variables measures moisture soil at different levels, thickness of the trunk of the plant and size of fruit, environmental measures such as relative humidity, temperature, speed and wind direction, and rainfall.